The use of biomarkers for the etiologic diagnosis of MCI in Europe: An EADC survey. Issue 2 (21st August 2014) - Bocchetta, Martina; Galluzzi, Samantha; Kehoe, Patrick Gavin; Aguera, Eduardo; Bernabei, Roberto; Bullock, Roger; Ceccaldi, Mathieu; Dartigues, Jean‐François; de Mendonça, Alexandre; Didic, Mira; Eriksdotter, Maria; Félician, Olivier; et al.
Abstract: We investigated the use of Alzheimer's disease (AD) biomarkers in European Alzheimer's Disease Consortium centers and assessed their perceived usefulness for the etiologic diagnosis of mild cognitive impairment (MCI). We surveyed availability, frequency of use, and confidence in diagnostic usefulness of markers of brain amyloidosis (amyloid positron emission tomography [PET], cerebrospinal fluid [CSF] Aβ42) and neurodegeneration (medial temporal atrophy [MTA] on MR, fluorodeoxyglucose positron emission tomography [FDG‐PET], CSF tau). The most frequently used biomarker is visually rated MTA (75% of the 37 responders reported using it "always/frequently") followed by CSF markers (22%), FDG‐PET (16%), and amyloid‐PET (3%). Only 45% of responders perceive MTA as contributing to diagnostic confidence, where the contribution was rated as "moderate". Seventy‐nine percent of responders felt "very/extremely" comfortable delivering a diagnosis of MCI due to AD when both amyloid and neuronal injury biomarkers were abnormal ( P  < .02 versus any individual biomarker). Responders largely agreed that a combination of amyloidosis and neuronal injury biomarkers was a strongly indicative AD signature.